IMPLIKASI PENDIDIKAN AGAMA ISLAM DALAM KELUARGA TERHADAP PERILAKU SISWA KELAS X MA DARUSSALAM PEKAT - Rosmiati; Ahmad Syagif; Trimansyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine: (1) the implementation of Islamic religiouseducation within the family and its influence on the behavior of tenth-grade studentsat MA Darussalam Pekat, and (2) the implications of Islamic religious educationwithin the family for the behavior of tenth-grade students at MA Darussalam Pekat.This research employed a qualitative method with a case study approach,conducted at MA Darussalam Pekat. The participants consisted of teachers,students, and parents. Data were collected through in-depth interviews, and theanalysis followed the Miles and Huberman interactive model. The findings indicatethat: (1). The implementation of Islamic religious education in the family takes placethrough three main aspects: daily religious practices, parental role modeling, andengagement in religious activities at home. However, the practice is not yetconsistent and largely depends on communication style, parental consistency, andthe family’s socio-economic conditions. (2). The implications of Islamic religiouseducation within the family are significant for students’ behavior. Most studentsdemonstrate religious attitudes, discipline, politeness, and strong learningmotivation, largely due to parental advice and role modeling. In conclusion, theimplications of Islamic religious education require strong cooperation between theschool, parents, and students to effectively build students’ character and behaviorbased on Islamic values.